The effect of training units with plyometric training on the development of frequent fast running for basketball players under 17 years old - Ben Hamidouche, Fayza; Mazari , Fatah (sports creativity, 2025)
This study aims to know the impact of the training units with the biometric training on the repeated fast running of basketball players, Where the study community included the mandate of M'sila, and the study sample was deliberately chosen and consisted of the UMB basketball team UMB and they also used the experimental approach and test the ability to repeat the speeds RSA, The study concluded that there is a positive impact of the biometric training on improving the player's